Factors affecting the escape of Sindbis virus from the Aedes aegypti midgut - Carpenter, Alexis Nicole Bair (Kansas State University, 2022)
Mosquito-borne arboviral diseases are a significant and expanding public health threat due to their ability to inflict considerable morbidity and mortality, and the increasing range of their vectors. Each arbovirus is often only able to be transmitted by certain vector species and this specificity, in part, is due to the presence of tissue and immunological barriers in the mosquito. An important tissue barrier that an arbovirus encounters is the midgut escape barrier. If a virus is unable to overcome a midgut escape barrier this means that neither disseminated infection nor transmission can occur. Unlocking the factors that contribute to this barrier could lead to new disease control strategies. In this work, we used the alphavirus Sindbis virus (SINV) and the mosquito vector Aedes aegypti to study how viral replication and apoptosis impact viral dissemination from the midgut. In our first study, we explored how viral midgut replication affects midgut escape. We developed SINV constructs designed to have reduced replication specifically in the midgut cells of Aedes aegypti by inserting sequences that are complementary to midgut-specific miRNAs into the 3′ untranslated region (MRE3′miRT) or the structural open reading frame (MRE-ORFmiRT) of the SINV genome. When mosquitoes were fed a blood meal containing one of these viruses or a control virus, nearly all fed with control viruses developed disseminated infection while significantly fewer mosquitoes developed disseminated infection with MRE3’miRT or MRE ORFmiRT. When mosquitoes did develop infection with one of the midgut replication restricted viruses, titers did not tend to be significantly different compared to controls. We also did not find evidence that a certain threshold titer needed to be reached in the midgut for dissemination to occur. Overall, these results suggest that viral replication within the midgut is an important factor in determining whether a mosquito will develop disseminated infection. In our next study we aimed to clarify the role of apoptosis in midgut escape. Several studies have shown that midgut apoptosis can negatively impact the ability of a virus to establish disseminated infection. However, contradictory evidence also exists. The goal of this study was to improve upon previous studies by generating a construct that more stably expressed the pro-apoptotic protein Reaper. A previous study showed that a virus that had the reaper gene inserted in the duplicated subgenomic promoter region (MRE/rpr) had reduced ability to cause disseminated infection in mosquitoes. However, this effect was short lived as it was found that mutations rapidly rendered Reaper nonfunctional. In order improve stability we inserted the reaper gene as an in-frame fusion into the structural open reading frame (ORF) of SINV. This construct, called MRE/rprORF, successfully expressed Reaper protein and induced apoptosis in both cell lines and mosquito midguts. Growth curves in BHK21 and C6/36 cells showed that MRE/rprORF replicated similarly to MRE/rpr. Mosquitoes fed with MRE/rprORF had less midgut and disseminated infection compared to mosquitoes fed with MRE/rpr or a control virus at all timepoints tested. Collectively, these studies show that reduced midgut replication and increased apoptosis negatively impact the establishment of midgut and disseminated infection in Aedes aegypti.
Keywords: Arbovirus; Alphavirus; Midgut escape barrier; Host-pathogen interactions; Aedes aegypti